A short biography of Hubert Ludwig and a note on the publication dates of his monograph Die Seewalzen (1889–1892) - Reich, Mike (Zootaxa, 2015)
The dates of publication of Hubert Ludwig’s (1852–1913) comprehensive monograph Die Seewalzen [= Sea cucumbers] are reviewed. The precise publication dates of his volume, originally published in 16 fascicles and 8 parts/issues, delivered between 1889 and 1892, has been re-examined. Additionally, a short biographical note on Hubert Ludwig's life and a discussion of all new taxa introduced by him in his monograph is given.